FISH AND FISHERIES OF THE CHILKA LAKE WITH STATISTICS OF FISH CATCHES FOR THE YEARS 1948-1950 - Jones, S; Sujansinghani, K H (Indian Journal of Fisheries, 2016)
THE faunistic investigations of the Chilka Lake conducted during 1914-15 by the Zoological Survey of India under the direction of late Dr. Nelson Annandale brought out the richness and variety of the fauna and the very remarkable ecological features associated with it. An exhaustive collection of fishes made during the survey was described by Chaudhury (1916 a, 1916 6; 1917 and 1923) and Hora (1923) and of the prawns and crabs by Kemp (1915).